Front Cover: Asymmetric Catalytic Approach to Multilayer 3D Chirality (Chem. Eur. J. 30/2021). Issue 30 (14th May 2021) - Wu, Guanzhao; Liu, Yangxue; Rouh, Hossein; Ma, Liulei; Tang, Yao; Zhang, Sai; Zhou, Peng; Wang, Jia‐Ying; Jin, Shengzhou; Unruh, Daniel; Surowiec, Kazimierz; Ma, Yanzhang; et al.
Abstract : Chirality has existed in nature from the early stages of life on Earth. A new form of chirality, multilayer 3D chirality, has been established involving nearly parallel patterns. This work presents the first asymmetric catalytic approach to multi‐layer 3D chirality. New complexes of Pd and chiral amide‐phosphine ligands were utilized as catalysts for Suzuki‐Miyaura coupling for assembling various multilayer 3D chiral molecules, which displayed strong luminescence under UV irradiation and strong aggregation‐induced emission (AIE) of different colors. More information can be found in the Full Paper by G. Li et al. (DOI: 10.1002/chem.202100700 ).